The Concept of “Territory” in Modern China: 1689-1910 - Christ, Stefan (2018)
There are two frequent misunderstandings in the scholarship on modern China’s territorial transformation. First, the concept of lingtu 领土 (“territory”) is often seen as only developing after the 1911 Revolution, in opposition to the earlier concept of jiangyu diguo 疆域帝国 (“imperial frontier”). Second, jiangyu and lingtu are often confused and seen as basically the same concept at different historical stages. This essay takes the translation and dissemination of “territory” before the 1911 Revolution as a starting point to examine how the basic concept of lingtu developed from a translated term to describe spatial relations into an important semantic resource of a political movement. On one hand, in the negotiations leading to the Treaty of Nerchinsk and in the modern treaty system, the translation of “territory” formed a new conceptual space, centred on lingtu, which differed from the idea of the (imperial) “frontier” (jiangyu). The turn from jiangyu to lingtu was not a complete one; rather, part of the old concept was integrated into the new framework. On the other hand, the concept of lingtu also provided a semantic battlefield, and the battle was already opened before the revolution: the earlier ideas, diplomatic relations and national narrative already formed the basic concepts dominating discourses after the revolution.<br
Keywords: territory; concept; translation; modern China